THE SOCIO-POLITICAL ENVIRONMENT IN THE PERIOD IN WHICH SHIHAB AL-DIN AL-SUHRAWARDI LIVED (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the socio-political environment of the Muslim East during the lifetime of Shihab al-Din Abu Hafs Umar al-Suhrawardi (1145–1234), the eponymous founder of the Suhrawardiyya Sufi order. It situates his career within the protracted decline of the Abbasid Caliphate, the political fragmentation that accompanied Buwayhid and Seljuk dominance, and the partial restoration of caliphal authority under al-Nasir li-Din Allah (r. 1180–1225). Particular attention is given to al-Nasir’s use of the futuwwa and of Sufi networks as instruments of political integration, and to al-Suhrawardi’s role as “Shaykh al-Shuyukh” and as the caliph’s diplomatic envoy to the Ayyubids, the Khwarazmshah, and the Seljuks of Anatolia. The study argues that al-Suhrawardi’s religious and political activity can be properly understood only against the background of the socio-economic crises and the search for social stabilization that characterized the late Abbasid period.
Keywords: Shihab al-Din al-Suhrawardi, Suhrawardiyya, Abbasid Caliphate, al- Nasir li-Din Allah, futuwwa, Sufism, Baghdad, socio-political history.